Identification of sites phosphorylated by the vaccinia virus B1R kinase in viral protein H5R - Brown, Neil G (BioMed Central, 2000)
BACKGROUND: Vaccinia virus gene B1R encodes a serine/threonine protein kinase. In vitro this protein kinase phosphorylates ribosomal proteins Sa and S2 and vaccinia virus protein H5R, proteins that become phosphorylated during infection. Nothing is known about the sites phosphorylated on these proteins or the general substrate specificity of the kinase. The work described is the first to address these questions. RESULTS: Vaccinia virus protein H5R was phosphorylated by the B1R protein kinase in vitro, digested with V8 protease, and phosphopeptides separated by HPLC. The N-terminal sequence of one radioactively labelled phosphopeptide was determined and found to correspond to residues 81-87 of the protein, with Thr-84 and Thr-85 being phosphorylated. A synthetic peptide based on this region of the protein was shown to be a substrate for the B1R protein kinase, and the extent of phosphorylation was substantially decreased if either Thr residue was replaced by an Ala. CONCLUSIONS: We have identified the first phosphorylation site for the vaccinia virus B1R protein kinase. This gives important information about the substrate-specificity of the enzyme, which differs from that of other known protein kinases. It remains to be seen whether the same site is phosphorylated in vivo.